2016
DOI: 10.3102/0034654315604027
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Children With Autism Spectrum Disorder With Restricted Interests

Abstract: Inclusive education requires teachers to adapt to childrenÕs learning styles. Children with autism spectrum disorder bring challenges to classroom teaching, often exhibiting interests restricted to particular topics. Teachers can be faced with a dilemma either to accommodate these restricted interests (RIs) into teaching or to keep them out of the classroom altogether. In this article, we examined all peer-reviewed studies of teaching children with autism spectrum disorder with RIs published between 1990 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 51 publications
1
63
1
2
Order By: Relevance
“…It has further been shown that individuals with ASD process information and learn differently to typicallydeveloping children (Gunn and Delafield-Butt, 2016). Effectively addressing the needs of those with ASD has implications for all aspects of educational provision: the school and classroom environment, the curriculum, teaching materials and teaching strategies (Barson, 2010).…”
Section: Teachers' Knowledge Regarding Asdmentioning
confidence: 99%
“…It has further been shown that individuals with ASD process information and learn differently to typicallydeveloping children (Gunn and Delafield-Butt, 2016). Effectively addressing the needs of those with ASD has implications for all aspects of educational provision: the school and classroom environment, the curriculum, teaching materials and teaching strategies (Barson, 2010).…”
Section: Teachers' Knowledge Regarding Asdmentioning
confidence: 99%
“…term outcomes (Mottron 2011). Crucially, I will delineate the ways in which school staff perceived this disposition, and demonstrate how, despite some drawbacks to this cognitive trait (Murray et al 2005;Gunn and Delafield-Butt 2016), their desired aims in providing support to the autistic children can be largely met by enabling them to access their strong interests. In addition, I will suggest how understanding better the manifestations and role of the intense interests of autistic children can shed light on the interests and motivations of all children in school (Schiefele 1991;Tomlinson et al 2003), potentially providing important understandings for the educational engagement and inclusion of whole school populations.…”
mentioning
confidence: 99%
“…The non-verbal nature of intersubjective relations, building narratives of meaning with patterned autonomic arousal and shared affect become cornerstones of a sensitive pedagogy that can capture the imagination and interest of children, even those with so-called behavioural difficulties, to help them to discover and find interest in learning (Delafield-Butt and Adie, 2015;. Such pedagogies, seek to support every child's interests and capacities to nurture and bring out the best in that child, and have sensitivity for whatever social or emotional difficulties they may have (Gunn and Delafield-Butt, 2016).…”
Section: Modern Prescriptions For Accepting Natural Impulses For Learmentioning
confidence: 99%